The Application Of Gamification-Based Learning Media To Student Interest In Learning PAI In Purwosari III Elementary School - Hikmah, Nurul; Jamhuri, M. (-, 2025)
Effective learning media must be in accordance with the nature of students and the learning objectives that have been set. A particular challenge at SDN Purwosari III is the low interest in learning students, especially in Islamic Religious Education. Due to the fact that learning usually focuses on lectures and lectures, a creative approach is needed to increase student engagement. The purpose of this study was to determine how using gamification-based learning media can increase students' interest in learning. Qualitative methods, using interviews and observations, were used to collect data. The results showed that gamification using components such as points, badges, challenges, and leaderboards can make learning more interesting, interactive, and healthy competitive. Students are more active, more motivated, and show increased participation and understanding of the material. Teachers can overcome challenges such as limited digital devices by being creative in creating game-based physical media. Therefore, gamification has proven to be an effective alternative to increase students' interest in learning, especially in Islamic Religious Education learning in elementary schools.